2020
DOI: 10.3390/vaccines8040562
|View full text |Cite
|
Sign up to set email alerts
|

Resident Memory T Cells and Their Effect on Cancer

Abstract: Resident memory T (TRM) cells are a unique subset of CD8+ T cells that are present within certain tissues and do not recirculate through the blood. Long term memory establishment and maintenance are dependent on tissue population of memory T cells. They are characterized by dual CD69/CD103 positivity, and play a role in both response to viral infection and local cancer immunosurveillance. Human TRM cells demonstrate the increased expression of adhesion molecules to facilitate tissue retention, have reduced pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 104 publications
1
14
0
Order By: Relevance
“…Generation of memory T cells is important for robust and durable tumor control. The presence of resident memory T cells within the tumor microenvironment is correlated with increased response to checkpoint inhibitors and survival [30,31]. Additionally, in a prior publication we showed that recurrent ovarian cancer patients MHC-II upregulation and TIS HIGH gene expression profile by NanoString at baseline had correlation with clinical benefit to Vigil [32].…”
Section: Results At 3 Years Of Follow-up Demonstrate Os and Rfs Advantage Tomentioning
confidence: 96%
“…Generation of memory T cells is important for robust and durable tumor control. The presence of resident memory T cells within the tumor microenvironment is correlated with increased response to checkpoint inhibitors and survival [30,31]. Additionally, in a prior publication we showed that recurrent ovarian cancer patients MHC-II upregulation and TIS HIGH gene expression profile by NanoString at baseline had correlation with clinical benefit to Vigil [32].…”
Section: Results At 3 Years Of Follow-up Demonstrate Os and Rfs Advantage Tomentioning
confidence: 96%
“…This hypothesis will require validation in future investigations. Previous studies have demonstrated the presence of resident memory T cells in some cancer patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis will require validation in future investigations. Previous studies have demonstrated the presence of resident memory T cells in some cancer patients(17).…”
Section: Discussionmentioning
confidence: 99%